Regulation of the Fanconi anemia DNA repair pathway by phosphorylation of FANCD2 - Kupculak, M (2020)
Living organisms have evolved multiple repair pathways that recognize and tackle different types of DNA damage. One such pathway is the Fanconi anemia DNA repair pathway which is able to repair DNA interstrand crosslinks (ICLs) – deleterious lesions arising by a covalent binding of the opposite DNA strands through a linker molecule. Of central importance to the ICL repair lies the FANCD2/FANCI heterodimer which is recruited to the site of the lesion and is subsequently monoubiquitinated by the Fanconi anemia core complex. These two steps are essential for the pathway to proceed and if they fail, so fails the entire repair. Due to its importance, FANCD2/FANCI is highly regulated by numerous post-translational modifications, phosphorylation being the best characterized.